2021
DOI: 10.3390/molecules26247665
|View full text |Cite
|
Sign up to set email alerts
|

HPLC/DAD, Antibacterial and Antioxidant Activities of Plectranthus Species (Lamiaceae) Combined with the Chemometric Calculations

Abstract: The increase in antibiotic resistance and the emergence of new bacterial infections have intensified the research for natural products from plants with associated therapy. This study aimed to verify the antibacterial and antioxidant activity of crude extracts of the genus Plectranthus species, being the first report on the modulation of aminoglycosides antibiotic activity by Plectranthus amboinicus extracts. The chemical composition was obtained by chemical prospecting and High-Performance Liquid Chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Several studies have reported that the structure of flavonoids structure is directly related to their capacity to reduce metals or to trap free radicals. It is affected by the number and positions of the hydroxy groups (−OH) [16] . Herein, compound 4 shows the highest antioxidant power due to the four hydroxy groups presented in its structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have reported that the structure of flavonoids structure is directly related to their capacity to reduce metals or to trap free radicals. It is affected by the number and positions of the hydroxy groups (−OH) [16] . Herein, compound 4 shows the highest antioxidant power due to the four hydroxy groups presented in its structure.…”
Section: Resultsmentioning
confidence: 97%
“…It is affected by the number and positions of the hydroxy groups (À OH). [16] Herein, compound 4 shows the highest antioxidant power due to the four hydroxy groups presented in its structure. Moreover the presence of an α,β-unsaturated group at C ring increases this activity.…”
Section: Antioxidant Activitymentioning
confidence: 95%
“…In a prior study, chemical analyses of species extracts from the Plectranthus genus revealed that chlorogenic acid is predominant in EELPa, while caffeic acid is the most prevalent compound in EELPb and EELPo. All these species demonstrated antibacterial efficacy against both Gram-positive and Gram-negative bacteria, indicating their potential for combating bacterial infections due to the presence of these chemicals ( Rodrigues et al, 2021 ).Additionally, other studies found that gallic acid and caffeic acid have the ability to reverse the resistance phenotype of Staphylococcus aureus, with caffeic acid efficiently inhibiting bacterial pumps in silico ( Dos Santos et al, 2018 , Lima et al, 2016 ). The presence of quercetin also exhibited enhanced antibacterial activity against Staphylococcus aureus ( Dos Santos et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds are the result of secondary metabolism in plants and are largely responsible for the antioxidant characteristics of a given extract ( Rodrigues et al, 2021 ). The presence of antioxidant compounds is important in extracts with pharmacological potential as it maintains the balance between pro and antioxidant substances.…”
Section: Discussionmentioning
confidence: 99%